2016
DOI: 10.1093/cid/ciw176
|View full text |Cite
|
Sign up to set email alerts
|

A Perfect Storm: Impact of Genomic Variation and Serial Vaccination on Low Influenza Vaccine Effectiveness During the 2014–2015 Season

Abstract: Using an integrated surveillance platform, we incorporated genetic, antigenic, and epidemiologic indicators to evaluate agent–host factors that contributed to low vaccine effectiveness during the 2014–2015 influenza season, including variation in the viral genome and negative effects of serial vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
176
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(195 citation statements)
references
References 39 publications
13
176
5
1
Order By: Relevance
“…Conversely, the observation of no residual protection from prior season vaccination was more consistent, with lower heterogeneity (I 2 = 48%, p = .1). Of note, two of three studies reported pronounced difference between repeated versus current season only vaccination during the 2014-2015 season [28,30], and this difference was statistically significant in one study [28]. Vaccine strains were unchanged and there was well-recognized mismatch between vaccine and epidemic strains, a pattern consistent with the antigenic distance hypothesis.…”
Section: H3n2mentioning
confidence: 69%
See 2 more Smart Citations
“…Conversely, the observation of no residual protection from prior season vaccination was more consistent, with lower heterogeneity (I 2 = 48%, p = .1). Of note, two of three studies reported pronounced difference between repeated versus current season only vaccination during the 2014-2015 season [28,30], and this difference was statistically significant in one study [28]. Vaccine strains were unchanged and there was well-recognized mismatch between vaccine and epidemic strains, a pattern consistent with the antigenic distance hypothesis.…”
Section: H3n2mentioning
confidence: 69%
“…Eighteen studies met the eligibility criteria [4,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Of these, one study was restricted to hospitalized patients and was therefore excluded from the meta-analysis [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2013-2014 season, LAIV VE against A/H1N1pdm2009 [3] (A/H1N1) was poor. Furthermore, the 2014-2015 season was characterized by the emergence of an A/H3N2 drifted virus that was associated with low VE in an early season estimate [4,5], and with an earlier-than-normal peak in influenza cases occurring in late December [6]. Thus, the unpredictability of influenza epidemiology continues to necessitate effectiveness studies of available influenza vaccines in a range of population subgroups.…”
mentioning
confidence: 99%
“…For all three seasons combined, a total of 111,580 respiratory specimens were tested for influenza with 16,135 (14.5%) testing positive 41% [14] (95% Confidence Interval, 17%-59%) -16% [9] (95% Confidence Interval, -49%-9%) * Reporting changes during the 2014/2015 influenza season likely resulted in under-reporting of the number of hospitalizations and deaths for that season †While the number of influenza A-positive specimens is based on PHOL data, the number of influenza A cases includes all laboratory-confirmed cases reported through the integrated Public Health Information System (iPHIS) by Ontario's public health units, which includes data from all laboratories in Ontario that test for influenza Figure 1 and Figure 2) ( Table 1).…”
Section: Comparison Of the Severity Of H3n2 Dominant Influenza Seasonsmentioning
confidence: 99%